Neuroprotective Potential of Fragaria nubicola Juice on Ischemia Reperfusion Induced Brain Injury in Rats - B. Rakhunde, Purushottam; Ali, Syed Ayaz; W. Khan, Subur (New Visions in Biological Science Vol. 8, 2022)
Without an effective treatment, brain stroke is one of the leading causes of death. Because of the presence of phenolic compounds, Fragaria nubicola has potential antioxidant activity and may be cytoprotective against ischemia-reperfusion brain injury. Fragaria nubicola is rich in ellagic acid and phenolic compounds. We investigated the effect of fresh fruit juice of Fragaria nubicola (10 ml/kg, p.o.) and vitamin E as a reference standard drug on 30 minutes of induced ischemia followed by reperfusion using neurobehavioral tests such as neurodeficit score, beam walk test, rota rod test, hanging wire test, and elevated plus maze. Nitric oxide, malondialdehyde, superoxide dismutase, and catalase were the biochemical parameters measured in the brains of control and treated rats. The fresh fruit juice of Fragaria nubicola treated groups improved neurobehavioral parameters such as motor performance [neurological status, significant increase in grasping ability (P<0.05), forelimb strength (P<0.05) improvement in balance and co-ordination (P<0.05)]. The biochemical parameters in rat brains revealed a significant increase in the activity of enzymatic antioxidants such as catalase (P<0.01), superoxide dismutase (P<0.01), significant reduction in the total nitrite (P<0.01) and lipid peroxidation (P<0.01). According to the findings, the juice of F. nubicola fruits (strawberry) has the most pronounced cytoprotective activity.